Impacto de la aplicación del sistema integrado de administración financiera (siaf-gl) en la planificación y ejecución presupuestal en la municipalidad distrital de santa: 2006-2010 - Ramos Méndez, Gonzalo Oliverio (2011)
The present study named: “FINANCIAL ADMINISTRATION INTEGRATED SYSTEM’S INCIDENCE (SIAF-SP), IN the BUDGETARY PROCESS’ PLANNING and IMPROVEMENT IN THE DISTRITAL MUNICIPALITY OF SANTA 2006-2010 ”; it is born from the present generalized problematic, in which the local governments do not use the financial resources assigned, and that in many cases, they give back the funds to the state treasury, stopping the making of elementary works to the detriment of their local communities. Nevertheless, we know that by mandate of the Peruvian government it has allow implements the Financial Administration’s Integrated System in the 1834 local governments in the country. But, most of these local governments does not count with the place or Office of Planning and Budget neither an efficient OCI. This is the reason why the present work of investigation tries to determine the incidence of SIAF- SP – Local Government in the planning and improvement of the budgetary execution’s processes in the Distrital Municipality of Santa. Also, to carry out the present study, period 2006-2010 has been considered, considering for the analysis, the documentary historical information of the Distrital Municipality of Santa. For the present study, the method has been considered analytical descriptive synthetic. And, for the analysis all the related elements and documentary information have been taken from the Distrital Municipality of Santa. Within the findings, we can stand out that the SIAF’s implementation, allows to improve the financial planning, the use of financial resources and also, to shorten times of transmission between the municipal budgetary’s formulation-execution and the Ministry of Economy and Finances. This, evidently, has invigorated the financial management of the Distrital Council of Santa.